REVIEW RAGAM JENIS KAPAL PERIKANAN INDONESIA - Axelius, Bradley; Kumara, I N. S.; Ariastina, W G. (Jurnal SPEKTRUM, 2022)
Indonesia as a maritime country with 2.23 million people working in the marine sector, one of which is a fisherman. Fishermen are one part of the fishing unit that plays a very important role for the success of a fishing operation. This paper reviews the fleet of vessels used by fishermen in Indonesia. The research method is a literature study taken from books, papers, the internet, and other sources that can support. The results of the review show that in carrying out fishing activities, fishermen in Indonesia use traditional and modern boats or boats. Types of boats or ships are divided into several categories. Depending on the type of fishing gear such as purse seine, trawls, dredge net, lift net, gill net, pole and line, long line, tonda ship, jungkung, and based on the propulsion system and ship size divided into powered boat and non-powered boat. In the operation of the ship, electricity is supplied by generators or batteries or batteries. To drive the sailing ship, a motorized engine is used, which is divided into inboard and outboard engines based on the layout, and is categorized into marine diesel engines and marineized engines based on their design and designation. On the other hand, to optimize the production of potential fisheries resources owned by Indonesia, it is necessary to increase the number of ships. The fluctuating growth in the number of vessels from 2002 to 2016, with the largest number of vessels amounting to 815,544 units in 2014 has not been able to maximize production from this potential. The Indonesian shipbuilding industry has also not developed in line with the challenges it faces. Development is still lagging behind the capacity, potential, demands and demands of the market. As well as social organizations also have an important role to increase capture fisheries production by providing guidanceThe information presented is expected to help the interests of the community such as the central government, local governments, researchers, students, and anyone who is interested in supporting the field of fishing vessels in Indonesia, especially the application of solar power plants on fishing boats.